Pore Development during the Carbonization Process of Lignin Microparticles Investigated by Small Angle X-ray Scattering - Rennhofer, Harald (Molecules, 2021)
Application of low-cost carbon black from lignin highly depends on the materials properties, which might by determined by raw material and processing conditions. Four different technical lignins were subjected to thermostabilization followed by stepwise heat treatment up to a temperature of 2000 °C in order to obtain micro-sized carbon particles. The development of the pore structure, graphitization and inner surfaces were investigated by X-ray scattering complemented by scanning electron microscopy and FTIR spectroscopy. Lignosulfonate-based carbons exhibit a complex pore structure with nanopores and mesopores that evolve by heat treatment. Organosolv, kraft and soda lignin-based samples exhibit distinct pores growing steadily with heat treatment temperature. All carbons exhibit increasing pore size of about 0.5–2 nm and increasing inner surface, with a strong increase between 1200 °C and 1600 °C. The chemistry and bonding nature shifts from basic organic material towards pure graphite. The crystallite size was found to increase with the increasing degree of graphitization. Heat treatment of just 1600 °C might be sufficient for many applications, allowing to reduce production energy while maintaining materials properties.